MEDICAL PROFESSIONALISM: A PANORAMIC VIEW THROUGH THE KALEIDOSCOPE OF STAKEHOLDER PERSPECTIVES - Khan, Junaid Sarfraz; Tabasum, Saima (Journal of Ayub Medical College Abbottabad, 2011)
Background: Recently, over the last couple of decades, great emphasis is being placed on the role of professionalism in medical education. This interest has intensified following the positive relationship identified between unprofessional behaviour in medical schools and subsequent practice. This paper aims to develop an understanding of the perceptions of various stakeholders regarding the subject in the local setting and tries to relate it to the global context. Methods: This was a qualitative study conducted in 2011 involving the faculty and students of the University of Health Sciences Lahore. An open-ended questionnaire was fashioned following brainstorming and utilising Delphi technique involving representatives of the students, faculty and the public. Responses from all the respondents were entered into Microsoft Excel data sheet and then imported into Qualitative Data Analysis Software '˜NVIVO 9'. Themes were extracted from the responses. Results: Overall 650 questionnaires were distributed amongst the faculty, students and general public. Response rates were 74%, 68% and 59% respectively. Commonalities and differences in the perceptions of the various stakeholders of medical profession including the medical practitioner, public and the medical students were identified. Conclusion: The product of the healthcare professional education system needs to conform to the global standards applied within local settings. It is the identification of the local setting that is critical to devising a costeffective and efficient curriculum, which amongst others includes teaching/training/learning and practice of professionalism. Keywords: Professionalism, Healthcare delivery, Medical Ethics, Behaviour, Community of Practice